RNAs in tumour-derived extracellular vesicles and their significance in the tumour microenvironment - Bugajova, Maria; Raudenska, Martina; Masarik, Michal; Kalfert, David; Betka, Jan; Balvan, Jan (International journal of cancer, 2024)
Small extracellular vesicles (sEVs) secreted by various types of cells serve as crucial mediators of intercellular communication within the complex tumour microenvironment (TME). Tumour-derived small extracellular vesicles (TDEs) are massively produced and released by tumour cells, recapitulating the specificity of their cell of origin. TDEs encapsulate a variety of RNA species, especially messenger RNAs, microRNAs, long non-coding RNAs, and circular RNAs, which release to the TME plays multifaced roles in cancer progression through mediating cell proliferation, invasion, angiogenesis, and immune evasion. sEVs act as natural delivery vehicles of RNAs and can serve as useful targets for cancer therapy. This review article provides an overview of recent studies on TDEs and their RNA cargo, with emphasis on the role of these RNAs in carcinogenesis.
Keywords: mezibuněčná komunikace; Humans; messenger RNA; RNA; RNA, Long Noncoding; kruhová RNA; MicroRNAs; RNA dlouhá nekódující; lidé; zvířata; Cell Communication; extracelulární vezikuly; RNA, Messenger; Neoplasms; Tumor Microenvironment; nádory; nádorové mikroprostředí; mikro RNA; Animals; RNA, Circular; Extracellular Vesicles